Pragmatic development in inmigrant`s interlanguage: the case of Haitians who study Spanish as a second language in Chile - Toledo Vega, Gloria (Lenguas Modernas, 2016)
This article presents an investigation about the pragmatic developmentin Spanish as second language (SSL) at oral and written level, and about thepragmatic consciousness in the interlanguage of Haitians immigrants in Chile. Theimportance of the sociopragmatic level to be immersed in the welcome communitywas considered to do this investigation, in which we analyzed the answers thatHaitians -from the initial and basic level of SSL- gave to written and oral playroles for requests, and also to questionnaires for judging the adequacy of somestatements in different situations. In order to determine a pragmatic development,this investigation was achieved in two phases, whose comparison showed that whileit is appreciated some evolution in the initial level, there are still some importantissues to teach after finishing SSL classes, which tend specially to better positioningHaitians immigrants in the local society